Analysis of the spatial patterns of poverty and development in Costa Rica: A statistical clusters study - Rodríguez Soto, Jorge (2024)
This paper aims to analyze the relationships between the different dimensions of poverty and development from a multidimensional and spatial perspective. Methodologically, this research is composed of two phases. The first, a descriptive statistics analysis of the Multidimensional Poverty Index and the Human Development one, was carried out, departing from the definitions of territoriality used in Costa Rica (rural-urban and by planning regions) with county-level data. In second place, a cluster analysis, with  K-means method, was developed with a database of 32 variables for development and poverty at the country level. About the results, we discovered that the typologies of rural and urban areas are significant but can be self-explanatory; the category of planning regions reveals relevant patterns in the center-periphery dynamics, particularly due to asymmetries between the center, the Pacific coast and, the Atlantic coast and borders. The cluster analysis confirms these patterns, showing that in terms of development, the country seems to be divided into 3 regions, while in terms of poverty is possible to identify 4. Concluding with some public and economic policy recommendations.